3D path planner of an autonomous underwater vehicle to track an emitter using frequency and azimuth–elevation angle measurements. Issue 8 (23rd June 2020) - Kim, Jonghoek
Abstract : This study considers the 3D scenario where an autonomous underwater vehicle (AUV) tracks an emitter while estimating the emitter's location by measuring the emitter's frequency and elevation–azimuth angle. To enhance the emitter estimation based on frequency–angle measurements, this study presents an AUV's path planner considering acceleration limits, such as the bounded turn rate. As far as the author's knowledge, the proposed path planner is novel in presenting an AUV's 3D path planner to enhance the emitter estimation based on frequency–angle measurements. The proposed 3D planner is useful in underwater target tracking, since the AUV approaches the emitter while avoiding 3D threat environments. The effectiveness of the proposed planner is verified by utilising simulations.